Peramalan Permintaan dalam Menentukan Penjualan Produk Menggunakan Metode DES Brown dan DES Holt di PT. XYZ - Santika Sari; Noiska Lathifa Sari; Jeremia Radja Moza; Dani Wahyudi; Mira Syehika Hutami (Universitas Teuku Umar, 2021)
PT XYZ is the first mining company in Indonesia engaged in the Alumina industry as well as an industrial pioneer in processing bauxite into CGA (Chemical Industry Alumina). The amount of demand for alumina varies depending on the number of product requests that must be produced each month. The methodology used in this research is forecasting. Forecasting is a method used to estimate a future need that refers to past data. The company's products are produced on a made-to-order system, and some are produced on a bespoke system developed to meet the needs of consumers or other companies. Currently, the problem experienced by PT XYZ is that it has only been reselling since late 2018, so it is still building brand and trust. And also the stock inventory is still very large so it still needs a lot of improvement and planning. So in this study, forecasting will be carried out to determine product sales using the DES Brown and DES Holt methods and find out which method is the best to use in helping to forecast product sales from PT XYZ. In this study, data plots were carried out and resulted in the type of Trend pattern. Furthermore, data forecasting is carried out using 2 methods, namely DES Brown and DES Holt. The best method used for forecasting this alumina demand is the Holt DES method with the accuracy of the calculation results using the smallest MAPE value. From the results obtained the smallest MAPE value is 0.246068 or 24.6%, meaning that the probability of success from forecasting is 75.6%.